THE ROLE OF CIVIL SOCIETY IN DEVELOPING GLOBAL CITIZENSHIP (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article considers the responsibility of civil society, experimenting with modelsof effective global citizenship, as well as deepening the understanding of the characteristics ofhumanity and the planet, caring for them and acting in their interests on the basis of environmentallyresponsible and socially inclusive principles and practical steps. Global citizenship is transformingthe worlds of art, business, culture, education, human and labor rights, religion, public health,politics, and our relationship with nature
Keywords: citizenship, concept, democracy, gender equality, Kyrgyzstan.